Citizenship in diverse societies - Kymlicka, Will; Norman, W. J. (Oxford University Press, 2000)
Is it possible to promote common bonds of citizenship while accommodating ethnocultural diversity? This work examines points of conflict & convergence between concerns for citizenship & diversity in democracies, reassessing & refining theories.